1996
DOI: 10.1017/s0022215100132736
|View full text |Cite
|
Sign up to set email alerts
|

Should nasopharyngeal biopsy be mandatory in adult unilateral glue ear?

Abstract: Unilateral secretory otitis media is a recognized presenting feature of nasopharyngeal neoplasia. In the two cases presented, biopsy from the nasopharynx revealed an unsuspected underlying adenocarcinoma. The need to biopsy the normal looking post-nasal space is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
5
1
1
Order By: Relevance
“…It is accepted that nasopharyngeal tumours may spread submucosally and that the nasopharynx may appear normal on flexible nasendoscopy. 5,6 However, in our study, no patient with a normal-looking nasopharynx proved to have a nasopharyngeal tumour on initial biopsy or at six month follow up.…”
Section: Discussioncontrasting
confidence: 62%
“…It is accepted that nasopharyngeal tumours may spread submucosally and that the nasopharynx may appear normal on flexible nasendoscopy. 5,6 However, in our study, no patient with a normal-looking nasopharynx proved to have a nasopharyngeal tumour on initial biopsy or at six month follow up.…”
Section: Discussioncontrasting
confidence: 62%
“…To date, two cases of NPC have been reported that were identified after the biopsy of a normal-looking nasopharynx in patients with isolated serous otitis media. 17 Furthermore, in three studies of 72, 275 and 169 patients presenting with serous otitis media, some of whom also had other symptoms, a tumour was identified in one patient with normal nasendoscopy findings in each study, with no other suspicious signs or symptoms in each study, representing 1.4 per cent, 0.4 per cent and 0.6 per cent incidence rates, respectively. 6,9,18 Conversely, in two studies of 85 and 57 patients with isolated serous otitis media, no tumours were identified in patients with normal nasendoscopy findings.…”
Section: Discussionmentioning
confidence: 95%
“…It is well accepted that it is not possible to exclude NPC by macroscopic examination of the nasopharynx alone, since nasopharyngeal tumours may spread submucosally, and that the nasopharynx may appear normal on flexible nasopharyngoscopy (31,32) . Therefore, if the clinical suspicion for nasopharyngeal malignancy is high, even if the suspected tumour cannot be visualized on endoscopic examination, other non-invasive techniques, such as MRI, should be used.…”
Section: Discussionmentioning
confidence: 99%